(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
Natural resources for flesh, fish, fowl and vegetation have an economic significance for early settlers, and are therefore discussed here. This is followed by a brief archaeological survey. Drowning of the coastline of the Western Isles has removed the evidence for coastal sites of the Mesolithic period. Neolithic evidence includes 34 megaliths and 7 occupation sites, while early Bronze Age settlement evidence is limited. In the later Bronze Age/early Iron Age 14 settlement mounds have been identified. The main focus of the archaeological survey is on the Iron Age. Structures, material culture and the evidence for metalworking are considered. Much of the material culture derives from eroding sand faces and is therefore without context although pottery has been recovered from archaeological sites.